Perlindungan Konsumen terhadap Risiko Algoritma AI pada Marketplace dan Fintech - Erlangga Dwi Putra; Dadan Taufik Fathurohman (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the legal provisions for consumer protection against the risks of using AI algorithms in Indonesia and examine the forms of business actors' responsibilities for resulting consumer losses. This study uses a normative juridical method with a legislative approach strengthened by interview data. The results show that legal protection for digital consumers is essentially regulated through the Consumer Protection Law and regulations related to electronic transactions. However, these regulations do not specifically address algorithm transparency, automated decision-making and AI accountability mechanisms. Furthermore, it was found that business actors remain responsible for losses arising from the AI systems used in their business activities. Therefore, more specific regulations are needed regarding algorithm transparency, digital accountability and consumer rights protection in the digital economy era.